2016
DOI: 10.1002/cbic.201600118
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gene Cluster for Chalcomycins and Aldgamycins: Genetic Basis for Bifurcation of Their Biosynthesis

Abstract: Aldgamycins are 16-membered macrolide antibiotics with a rare branched-chain sugar d-aldgarose or decarboxylated d-aldgarose at C-5. In our efforts to clone the gene cluster for aldgamycins from a marine-derived Streptomyces sp. HK-2006-1 capable of producing both aldgamycins and chalcomycins, we found that both are biosynthesized from a single gene cluster. Whole-genome sequencing combined with gene disruption established the entire gene cluster of aldgamycins: nine new genes are incorporated with the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The molecular formulas of compounds 7 and 8 were established as C 34 H 56 O 14 and C 34 H 54 O 14 by the quasi‐molecular ions at m / z 711.3572 [ M +Na] + and 709.3397 [ M +Na] + in HR‐ESI‐MS, which were 14 amu (CH 2 ) fewer than for 3 and 4 , respectively. The 1 H and 13 C NMR spectra of 7 were very similar to those of 3 except that the signal of a methoxy group [ δ C =56.7 ppm/ δ H =3.42 ppm (3 H, S)] linked to C‐3′ in 3 was not observed in 7 , and there was a significant upfield shift of C‐3′ in 7 compared to 3 (from δ C =80.5 ppm to δ C =71.2 ppm), thus implying that the C‐3′ methoxy group in 3 had become a hydroxy group in 7 . Moreover, the structure of 7 was further confirmed by 2D NMR analyses (Table S3 ), with the assignments of all proton and carbon resonances provided in Table .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The molecular formulas of compounds 7 and 8 were established as C 34 H 56 O 14 and C 34 H 54 O 14 by the quasi‐molecular ions at m / z 711.3572 [ M +Na] + and 709.3397 [ M +Na] + in HR‐ESI‐MS, which were 14 amu (CH 2 ) fewer than for 3 and 4 , respectively. The 1 H and 13 C NMR spectra of 7 were very similar to those of 3 except that the signal of a methoxy group [ δ C =56.7 ppm/ δ H =3.42 ppm (3 H, S)] linked to C‐3′ in 3 was not observed in 7 , and there was a significant upfield shift of C‐3′ in 7 compared to 3 (from δ C =80.5 ppm to δ C =71.2 ppm), thus implying that the C‐3′ methoxy group in 3 had become a hydroxy group in 7 . Moreover, the structure of 7 was further confirmed by 2D NMR analyses (Table S3 ), with the assignments of all proton and carbon resonances provided in Table .…”
Section: Resultsmentioning
confidence: 90%
“…The resulting plasmid was then transformed into Streptomyces sp. HK‐2006‐1 by intergeneric conjugation as described previously . Successful knock‐out of the almCII gene in a clone named JHZ1007 was confirmed by genotyping PCR with primers almCII ‐EcoRI‐F and almCII ‐BamHI‐R.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among our recent discoveries [11,12,13,14,15,16,17,18,19,20,21], we recently reported that a strain of Streptomyces sp. HK-2006-1 produced both aldgamycins and chalcomycins, which are 16-membered macrolides [11,21]. Chalcomycin and seven aldgamycins were isolated from this strain, and chalcomycin showed more potent antibacteria activity against Staphylococcus aureus than aldgamycins [11].…”
Section: Introductionmentioning
confidence: 99%